Discours scientifique et littérature. Approche de la citation chez Martin Winckler - Fabienne Gooset (Parole Rubate, 2014)
This article examines the function of quotation in two novels by Martin Winckler. Referring to Antoine Compagnon's critical suggestions, I have tried to distinguish between the function of long quotations and shorter ones. Being dialectically linked to the text that cites them, long citations draw on the reader's sensitivity and personal interpretation. Short citations, instead, regularly interwoven with the narrative stream, are like a revealing Ariadne's thread.